Linking ESG to Tax Avoidance: Do Women Directors Matter? - Sibuea, Dewi Paskah; Afriani, Cynthia (Sekolah Tinggi Manajemen IPMI, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance on tax avoidance, as well as the moderating role of female board representation in this relationship. The research uses data from manufacturing firms listed in ASEAN-5 countries during the 2019–2023 period. The analysis is conducted using a dynamic panel regression method with a two-step System Generalized Method of Moments (System GMM) approach and robust standard errors to address potential endogeneity and autocorrelation. The results indicate that ESG performance does not have a statistically significant effect on tax avoidance. The interaction term between ESG and the presence of female directors, which represents the moderating effect, is also statistically insignificant, although it shows a negative direction. Additionally, control variables such as profitability, leverage, firm size, market-to-book ratio, and economic growth do not exhibit significant effects. These findings suggest that neither ESG implementation nor board gender diversity currently functions as an effective control mechanism for tax avoidance practices in the ASEAN-5 manufacturing sector. Therefore, enhancing ESG practices and empowering women in corporate governance structures remains essential for promoting better tax compliance in the long term.